ANALISIS KORELASI ANTARA KEPUASAN KERJA DENGAN KARYAWAN : STUDI PADA PT. MULTI KARYA ABDILLAH LINES SAMARINDA - Riadi, Selamat (PREDIKSI, 2012)
This study aimed to determine whether the Job Satisfaction has a positive correlation with the performance of employees at PT. Multi Lines of Work Abdillah Samarinda. The results showed that there is a positive and significant relationship between the variables with the variable Job Satisfaction Employee Performance At PT. Multi Lines of Work Abdillah Samarinda. It inidapat known from the results of statistical tests in which the correlation coefficient (r) is equal to 0.658, which means there is a strong and positive relationship between the two variables, because the result is greater than the table of critical prices Product Moment Correlation coefficients (Pearson) for n = 20 at the 5% significance level, yaitu0, 444 or it can also be said that rhit = 0.658> = 0.444 rtab Meanwhile if the results were compared with tables provide guidelines for the interpretation of the Product Moment Correlation coefficient, as stated in Chapter III, the results the calculations are in the interval from 0.60 to 0.799, which means that there is a strong relationship between the variables Job Satisfaction with the performance variable.